Relevansi Fatwa Mazhab Syafi’i Tentang Kufu Dalam Nikah Terhadap Kompilasi Hukum Islam (KHI) - Hasan Bashori; Cipto Sembodo (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2018)
This article aims to examine the fatwa of kufu from the famous Shafi'i school and its relevance to the marriage regulations in Indonesia, specifically the Compilation of Islamic Law (KHI). This library research also uses fatwa comparisons between schools and comparison between laws and regulations to obtain data. In Islamic law, it is not permissible to prevent marriage just because of different kufu. The kufu law is excluded in terms of religion because it can bring household into disharmony. This, in the end, turned out to be recognized both in the fatwa of Shafi'i schools and KHI.